Idioblasts formation and essential oil production in irrigated Piper aduncum - Pires Jacinto, Ana Carolina; Souza, Leonardo Paula de; Nakamura, Adriana Tiemi; Carvalho, Fabio Janoni; Simao, Edson; Zocoler, Joao Luis [UNESP]; Bergo, Celso Luis (Univ Federal Goias, 2018)
The growing of Piper aduncum for essential oil extraction has increased, but there is a lack of basic information about its management and cultivation, which allows the productivity and quality of the oil, in order to attend the market demands. This study aimed to evaluate the relation between the production of essential oils from P. aduncum and soil water pressure heads (20 kPa, 40 kPa, 60 kPa, 100 kPa and non-irrigated). The assessment comprised the quantification of idioblasts and the production of essential oil extracted from leaves of cultivated plants. The variation in the soil water pressure head alters the amount of idioblasts in P. aduncum leaves, with impacts on the essential oil production. A soil water pressure head range of 20-60 kPa is sufficient for this species to express the highest amount of idioblasts and the highest level of essential oil production. The species adapts itself to different water availability conditions in the soil. Under stress conditions, due to water deficit or excess, the production of essential oil is reduced.